Prevalence and evolution of snoring and the associated factors in two-year-old children - Katila Maija; Saarenpää-Heikkilä Outi; Saha Marja-Terttu; Vuorela Nina; Huhtala Heini; Korhonen Laura S; Lukkarinen Minna; Tuulari Jetro J; Karlsson Linnea; Karlsson Hasse; Paavonen E Juulia (Netherlands, 2022)
Abstract
Objectives
To evaluate the prevalence and persistence of snoring during the first two years of life in two Finnish birth cohorts and to assess the associated factors.
Study design
The study population comprised 947 children from the CHILD-SLEEP (CS) and 1393 children from the FinnBrain (FB) birth cohorts. Questionnaires were provided to both parents when the child was 24 months of age. The questionnaire consisted of parts concerning the child's sleep and environmental factors.
Results
The combined prevalence of habitual snoring in the two birth cohorts at the age of 24 months was 2.3% (95% CI 1.5–3.1), which is markedly lower than reported previously.
Children suffering from recurrent infections (CS odds ratio (OR) 3.9, 95% CI 1.2–12.5) or asthma (FB OR 4.3, 1.4–13.5) snored habitually more often. Both the mother's (CS OR 3.2, 1.2–9.0) and father's (CS OR 3.4, 1.4–8.0) snoring every night added to the risk of the child snoring. In the multivariate models, parental snoring (CS adjusted odds ratio (ORa) 2.8, 1.1–6.8), the mother's lower level of education (CS ORa 2.9, 1.2–7.5, FB ORa 2.1, 1.0–4.5), and the mother's lower monthly income (FB ORa 2.9, 1.3–6.3) associated with the child's habitual snoring.
Conclusions
The prevalence of habitual snoring in two Finnish birth cohorts is lower than reported previously. The independent risk factors for habitual snoring at the age of two years were the parents' snoring and the mother's low income and low education.